Virtual Pesantren: Pesantren Sustainability in Facing the Challenges of 4.0 Era - Moh. Rifqi Rahman; Hanun Asrohah (Program Pascasarjana Universitas Ibrahimy, 2022)
Pesantren is proven to have high resilience and adaptability. This is evidenced by its development which is so dynamic that it can exist to this day. Pesantren has to deal with the challenges of this 4.0 era which is so synonymous with automation due to the birth of technology, digitization, intelligent technology, the speed of information flow, and so on. However, pesantren is still able to adapt until finally, new variants of pesantren appear, such as virtual pesantren. The birth of this virtual pesantren is really clear evidence that pesantren can maintain its sustainability amid this sophisticated era, although on the one hand it must be admitted that virtual pesantren is not fully capable of displaying the character of pesantren as a whole, including in terms of learning. Thus, pesantren continuously tries to adapt themselves to the times and seeks to utilize technology as a tool to support the goals of the pesantren itself. Virtual pesantren is an example of the phenomenon of how pesantren survive and adapt to this 4.0 era.